A narrative review of the potential for self‐tanning products to substitute for solaria use among people seeking a tanned appearance. Issue 2 (23rd January 2014) - Paul, Christine L.; Bryant, Jamie; Turon, Heidi; Brozek, Irena; Noble, Natasha; Zucca, Alison
Summary Skin cancers including melanoma and non‐melanoma skin cancers are a high‐cost and largely preventable form of cancer. While limiting exposure to solar ultraviolet (UV) light via outdoor activities is a focus of public health efforts, indoor UV exposure via solaria or 'tanning booths' has also become a cause for concern. In recent decades the availability of less harmful non‐UV self‐tanning products such as sprays and lotions has increased. This review explores (i) the available data regarding the prevalence and behavioural factors associated with use of solaria and self‐tanning products and (ii) data that may shed light on the likelihood of solaria users substituting self‐tanning products as a less harmful alternative to solaria exposure. While there are insufficient data on which to draw a firm conclusion about the potential for substitution, it appears unlikely that most solaria users would readily substitute self‐tanning products in place of solaria exposure. Public health advocates may need to consider whether a robust research study of the cost‐effectiveness of encouraging substitutional use of self‐tanners is desirable, or whether efforts to severely restrict access to solaria may be a better approach.